Uremic Toxin p-Cresyl Sulphate Induces Osteoblast Death and Inflammation in Chronic Kidney Disease Without Affecting Bone Marker Expression - Gabriele Ruth Anisah, Froemming; Ahmad Faizal, Jelani; Dayang Erna Zulaikha, Awang Hamsin; Mohammad Zulkarnaen, Ahmad Narihan (2025)
p-Cresyl Sulphate (pCS), a protein-bound uremic toxin, accumulates in the blood of patients with chronic kidney disease (CKD). Uremic toxins in general have emerged as a potential cause for CKD-associated bone mineral loss. Osteoblasts, specialized bone-forming cells, play an important role in bone development and remodelling. This study aimed to investigate the changes in bone markers as well as the apoptotic and inflammatory alterations in human foetal osteoblast 1.19 (hFOb 1.19) cells upon exposure to pCS. Exposure to pCS reduced osteoblast cell viability, increased the release of IL6 and IL1b while not significantly disturbing the RANKL/OPG ratio and the release of bone markers like osteocalcin and ALP. Using the Cell Counting Kit-8 (CCK-8) assay, we assessed the cell viability and with the help of various ELISA kits we observed that pCS increased the expression of Caspase-8 (CASP-8), Caspase-12 (CASP-12) and BCL-2 Associated X (BAX) protein indicating cell death via induction of apoptosis in osteoblasts. pCS exposure also showed an increase of inflammatory markers like Interleukin-6 (IL-6) and Interleukin-1 (IL-1 ), indicating a heightened inflammatory response in osteoblasts and a potential induction of osteoclastogenesis. These findings highlight the potential of pCS and possibly other uremic toxins to induce inflammation and bone loss in CKD patients. Future research should focus on identifying the specific molecular pathways in which pCS exerts its toxic effects so that potential therapies can be developed.